Decoding (patho-)physiology of the lung by advanced in vitro models for developing novel anti-infectives therapies. Issue 1 (January 2021) - Montefusco-Pereira, Carlos Victor; Carvalho-Wodarz, Cristiane de Souza; Seeger, Johanna; Kloft, Charlotte; Michelet, Robin; Lehr, Claus-Michael
Graphical abstract: Highlights: Pulmonary cell and tissue models are important tools for pulmonary drug delivery. Advanced lung models must mimic not only the health but also the diseased state. Long-term infection models feature biofilms, immune response and aerosol deposition. Novel anti-infectives benefit from combined in vitro and pharmacometric models. The need for novel anti-infective therapies is dramatically increasing, not only for viral but also for bacterial infections and antimicrobial resistance. This is especially true for chronic lung infections, typically occurring during e.g., cystic fibrosis (CF). Mimicking the structure and physiology of the diseased lung, advanced in vitro models also allow studying the pathophysiological changes relevant to microbial growth, drug resistance, and biofilm formation. Combining data from such advanced in vitro models with pharmacometric approaches may enable mechanistic explanation of the PK/PD drug exposure-response relationship and facilitate the translation to an in vivo setting. Teaser: Advanced lung cell culture models provide physiologically-relevant and complex data for mathematical models to exploit host-pathogen responses during anti-infective drug testing.